MENINGKATKAN KEMAMPUAN READING SISWA DENGAN METODE PHONICS APPROACH PADA SISWA KELAS TUJUH (VII) MTS NW TANAK BEAK BARAT - Rosyidi, Ahmad Zuhri; Suryadi, Hendra; Paris, Atika Salman; Yulandari, Evi safitri (Devote: Jurnal Pengabdian Masyarakat Global, 2022)
Reading ability is an important skill that has to be acquired by students, especially in English. Regardless of that fact, we from Institut Pendidikan Nusantara Global team took initiative to conduct training that can assist students to overcome students reading ability by the theme Teaching Reading—Based Phonics Approach. This activity is carried out at the seventh graders (VII) of MTs NW Tanak Beak Barat. The methods we used in this community service are observation, socialization with the school stockholders, and doing the program. The result of this program is that there is an improvement in students’ reading ability at the seventh graders (VII) of MTs NW Tanak Beak Barat. In addition, there is an improvement in the students’ motivation after learning English through Phonics—Based Approach, so that students are not pressured and enjoy the learning activity.